2010
DOI: 10.1002/pros.21283
|View full text |Cite
|
Sign up to set email alerts
|

Use of irinotecan for treatment of small cell carcinoma of the prostate

Abstract: Tumor tissue lines established via subrenal capsule xenografting provide models with clinical relevance and the present study suggests that irinotecan could be useful for therapy of refractory prostatic SCC, in particular in combination with cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…In a phase III trial, the combination of 5-fluouracil, leucovorin, oxaliplatin, and irinotecan resulted in better responses, progression-free survival, and overall survival when compared with the standard single drug therapy with gemcitabine for metastatic pancreatic ductal adenocarcinoma [97]. In small-cell prostatic carcinoma, irinotecan promoted an increase in autophagy of treated tumors as indicated by an increase in LC3B expression [98, 99]. Nevertheless, authors of this research state that the role of autophagy is complex.…”
Section: The Reverse Warburg Effect In Cancer: Pharmacological Modmentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase III trial, the combination of 5-fluouracil, leucovorin, oxaliplatin, and irinotecan resulted in better responses, progression-free survival, and overall survival when compared with the standard single drug therapy with gemcitabine for metastatic pancreatic ductal adenocarcinoma [97]. In small-cell prostatic carcinoma, irinotecan promoted an increase in autophagy of treated tumors as indicated by an increase in LC3B expression [98, 99]. Nevertheless, authors of this research state that the role of autophagy is complex.…”
Section: The Reverse Warburg Effect In Cancer: Pharmacological Modmentioning
confidence: 99%
“…In general, as mentioned before, a considerable amount of caution should be exercised for the interpretation of the consequences of cancer chemotherapy on autophagy. Other chemotherapeutic agents like the glycoside oleandrin, some platinum compounds, the multikinase inhibitor sorafenib, and some histone-deacetylase inhibitors have demonstrated effects on the autophagy rate in pancreatic carcinoma cell lines [98, 99]. As proposed, autophagy may be involved in carcinogenesis, tumor progression, and dissemination and may be associated at least in part with the actions of some chemotherapy for pancreatic ductal adenocarcinoma as well.…”
Section: The Reverse Warburg Effect In Cancer: Pharmacological Modmentioning
confidence: 99%
“…To overcome this hurdle, we have developed transplantable, metastatic and nonmetastatic patient-derived prostate cancer tissue xenograft lines in NOD-SCID (nonobese diabetic/severe combined immunodeficient) mice. The subrenal capsule grafting technique used to develop such cancer tissue lines tends to retain important properties of the original cancers, including histopathology, chromosomal aberrations and gene expression profiles, resulting in xenograft lines that closely resemble the original cancers 789. Recently, we have developed paired metastatic (LTL-313H) and nonmetastatic (LTL-313B) prostate cancer sublines from one patient's specimen, that are suitable for investigating the molecular basis of metastasis 10…”
Section: Introductionmentioning
confidence: 99%
“…Use of LTL352, a transplantable tissue line developed from a patient's NEPC specimen, has indicated that irinotecan, a topoisomerase I inhibitor, is potentially useful for therapy of refractory NEPC, in particular in combination with cisplatin 60. Recently the LTL352 model was also used to determine the efficacy of a new aurora kinase inhibitor, PHA-739358, in NEPC 61.…”
Section: Applications Of Next Generation Prostate Cancer Xenograft Momentioning
confidence: 99%